Mixing audio : concepts, practices and tools - Izhaki, Roey. (Oxford [u.a.] Focal Press, 2012)
Your mix can make or break a record, and mixing is an essential catalyst for a record deal. Professional engineers with exceptional mixing skills can earn vast amounts of money and find that they are in demand by the biggest acts. To develop such skills, you need to master both the art and science of mixing. The new edition of this bestselling book offers all you need to know and put into practice in order to improve your mixes. Covering the entire process --from fundamental concepts to advanced techniques -- and offering a multitude of audio samples, tips and tricks, this book has it all. Roey Izhaki teaches you the importance of a mixing vision, how to craft and evaluate your mix and then take it a step further. He describes the theory and the tools used and how these are put into practice while creating mixes. Packed full of photos, graphs, diagrams and audio samples, Mixing Audio is a vital read for anyone wanting to succeed in the field of mixing. New to this edition: * Multitracks provided to help practice mixing * Fully updated with current plug-in and software version and information * Companion website with a multitude of new samples including more macro-mixing samples * A new sample mix: Rock n' Roll * Rounded, extensive and complete coverage of music mixing * Includes a Web site with over 700 audio samples and 8 sample mixes * Covers new topics and mixing trends such as computer centered mixing
Introduction -- Part I: Concepts and Practices -- Music and mixing -- Music -- an extremely short introduction -- The role and importance of the mix -- The perfect mix -- Some axioms and other gems -- Louder perceived better -- Percussives weight less -- Importance -- Natual vs. artificial -- Learning to mix -- What makes a great mixing engineer? -- Methods of learning -- Mixing analysis -- Reference tracks -- The process of mixing -- Mixing and the production chain -- The mix as a composite -- Where to start? -- Deadlocks -- Milestones -- Finalizing and stabilizing the mix -- Related issues -- How long does it take? -- Breaks -- Using solos -- Mono listening -- Bouncing -- Housekeeping -- Mix Edits -- Mastering -- Mixing domains and objectives -- Mixing objectives -- Frequency domain -- Level domain -- Stereo domain -- Depth -- Part II: Tools -- Monitoring -- How did we get here? -- Choosing monitors -- The room factor -- Positioning monitors -- Meters -- Peak meters -- Average meters -- Phase meters -- Mixing consoles -- Processors vs. effects -- Basic signal flow -- Groups -- In-line consoles -- The monitor section -- Solos -- Correct gain structure -- The digital console -- Software mixers -- Tracks and mixer strips -- Routing -- The internal architecture -- Phase -- What is phase? -- Problems -- Tricks -- Faders -- Types -- Scales -- Working with faders -- Panning -- How stereo works? -- Pan controls -- Types of tracks -- Panning techniques -- Beyond pan pots -- Equalizers -- Applications -- The frequency spectrum -- Types and controls -- In practice -- Equalizing various instruments -- Introduction to dynamic range processors -- Dynamic Range -- Dynamics -- Dynamic Range Processors in a nutshell -- Compressors -- Principle of operation and core controls -- Additional controls -- Controls in practice -- Applications -- Tricks -- More on compressors -- Limiters -- Gates -- Controls -- Applications -- In practice -- Tricks -- Expanders -- Controls -- In practice -- Upward Expanders -- Duckers -- Operation and controls -- Applications -- Delays -- Delay basics -- Types -- In practice -- Applications -- Other modulation tools -- Vibrato -- ADT -- Chorus -- Flanging -- Phasing -- Tremolo -- Reverbs -- Applications -- Types -- Reverb programs -- Reverb properties and parameters -- Reverbs and stereo -- Other reverb types -- Reverbs in practice -- Distortion -- Distortion basics -- Ways to generate distortion -- Drum Triggering -- Methods of drum triggering -- Other tools -- MS -- Pitch shifters and harmonizers -- Exciters and enhancers -- Transient designers -- Automation -- The automation process -- Automation alternatives -- Control surfaces -- Part III: Sample Mixes -- Hero (rock) -- The Hustler (drum n' bass) -- Temps (hip hop) -- Donna Pomini (dance) -- Appendices -- Appendix 1: Notes and frequencies -- Appendix 2: Delay time chart.
Includes index
Previous ed.: 2008
Keywords: Sound -- Recording and reproducing -- Digital techniques; Sound recordings -- Production and direction; Sound -- Recording and reproducing -- Digital techniques; Sound recordings -- Production and direction